Analisis Struktur Cerita Pendek Karya Siswa Kelas IX - Syarif, Ganesia Dwi Astuti (Jurnal Guru Indonesia, 2023)
AbstractThis study aims to find out the ability of students in writing short stories by analyzing the structure of short stories that have been produced by students. This research uses a qualitative research type. This study describes qualitative data in the form of written data from short stories by class IX students at MTS Al-Ishlah Bobos, Cirebon Regency. The study used a descriptive research design. The source of the data in this study is the student's short story text. The sample used in this study amounted to 15 students in class IX A. The technique used in this study was to observe, listen and take notes. A short story is said to be perfect if it has an appropriate text structure, namely abstract, orientation, complication, evaluation, resolution and code. Found 5 short story texts that have an abstract structure, 13 short story texts that have a complication structure, 11 short story texts that have an evaluation structure, 12 short story texts that have a resolution structure, and 9 short story texts that have a code structure. This means that students do not understand the proper structure of the short story text. Then make learning evaluation instruments by paying attention to KD, then indicators. Indicators have an important role in preparing the learning process. Penelitian ini bertujuan untuk mencari tahu kemampuan siswa dalam menulis cerpen dengan menganalisis struktur cerpen yang telah dihasilkan oleh siswa. Penelitian ini menggunakan jenis penelitian kualitatif. Penelitian ini memaparkan data kualitatif berupa data tertulis dari teks cerpen karya siswa kelas IX MTS Al-Ishlah Bobos Kabupaten Cirebon. Penelitian menggunakan desain penelitian deskriptif. Sumber data dalam penelitian ini adalah teks cerpen siswa, sampel yang digunakan dalam penelitian ini berjumlah 15 siswa di kelas IX A. Teknik yang digunakan dalam penelitian ini dengan melakukan teknik observasi, simak dan catat. Cerpen dikatakan sempurna jika cerpen tersebut mempunyai struktur teks yang sesuai yaitu abstrak, orientasi, komplikasi, evaluasi, resolusi dan koda. Ditemukan 5 teks cerpen yang terdapat struktur abstrak, 13 teks cerita pendek yang terdapat struktur komplikasi, 11 teks cerita pendek yang terdapat struktur evaluasi, 12 teks cerita pendek yang terdapat struktur resolusi, dan 9 teks cerpen yang terdapat struktur koda. Hal tersebut siswa dianggap kurang memahami tentang struktur teks cerpen yang tepat. Kemudian Membuat instrumen evaluasi pembelajaran dengan cara memperhatikan KD, kemudian indikator. Indikator mempunyai peran yang penting dalam mempersiapkan proses pembelajaran.